Richard Serra - Foster, Hal.; Hughes, Gordon, 1965-; Buchloh, B. H. D. (Cambridge, Mass. : MIT Press, 2000)
A critical primer on artist Richard Serra's work. Richard Serra is considered by many to be the most important sculptor of the postwar period. The essays in this volume cover the complete span of Serra's work to date--from his first experiments with materials and processes through his early films and site works to his current series of "torqued ellipses." There is a special emphasis on those moments when Serra extended aesthetic convention and/or challenged political authority, as in the famous struggle with the General Services Administration over the site-specific piece Tilted Arc. October Files October Files is a new series of inexpensive paperback books. Each book will address a body of work by an artist of the postwar period who has altered our understanding of art in significant ways and prompted a critical literature that is sophisticated and sustained. Each book will trace not only the development of an important oeuvre but also the construction of the critical discourse inspired by it. The series editors are Hal Foster, Benjamin H.D. Buchloh, Annette Michelson, Yve-Alain Bois, and Rosalind Krauss
Process sculpture and film in the work of Richard Serra (1978) / Benjamin H.D. Buchloh -- The films of Richard Serra : an interview (1979) / Annette Michelson -- A picturesque stroll around Clara-Clara (1983) / Yve-Alain Bois -- Richard Serra : sculpture (1986) / Rosalind Krauss -- Redefining site specificity (1986) / Douglas Crimp -- The un/making of sculpture (1998) / Hal Foster.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Serra, Richard, -- 1938-2024 -- Criticism and interpretation; Serra, Richard, -- 1939- -- Critique et interprétation.; Serra, Richard, -- 1938-; ART -- Sculpture & Installation; ARTS/General; Electronic books; Criticism, interpretation, etc